The emergence of the creative ager – On subject cultures of late-life creativity - Gallistl, Vera (Journal of aging studies, 2018)
In the last fifteen years, research on aging has seen a new interest in creativity in later life. While late-life creativity has often been described as a method to unpack the potential of older adults in the face of demographic change, this newfound interest is arguably linked to the commodification of late-life creativity itself in terms of innovation and productivity. These new modes of creativity might then also establish new ways to age. Has the homo aestheticus spread into old age? To explore this question, this paper first lays out a praxeology of late-life creativity. In this framework, creativity as well as age is understood as a social practice through which the artwork as well as the (older) artist is continuously produced. Second, this paper draws upon data from thirteen semi-structured interviews with older adults regularly involved in creative practices in their everyday lives. Using the documentary method, data shows how older adults describe the creative practice and what meanings they attach to growing older within these practices. Analyzing subject cultures that emerge from creativity in later life shows how creative practice calls for a specific self-image that is centered around productivity, the preservation of field positions despite growing older and active as well as anti-aging. Studying late-life creativity through a praxeological lens allows for critically evaluating current modes of creativity and the normative positions that are inherent in these practices. •Late-life creativity is commodified in terms of productivity and innovation•Subjectivities arising from late-life creativity focus on active and anti-aging•Creativity is an arena in which age relations are negotiated and regulated